Covalent organic frameworks and electron mediator-based open circuit potential biosensor for in vivo electrochemical measurements. Issue 35 (24th August 2018) - Su, Dan; Feng, Bingwei; Xu, Pengfei; Zeng, Qiang; Shan, Baixi; Song, Yonggui
Abstract : Schematic illustration of the structure of GOD/DMFc/COF-LZU1/CFMEs and the analytical principles of OCPS. Abstract : This study demonstrates the first exploitation of covalent organic frameworks (COFs), which have good biocompatibility as the matrix for constructing integrated electron mediator-based open circuit potential biosensors (OCPS) for in vivo measurement of neurochemicals, such as glucose. In this study, we find that COFs are able to serve as a matrix for co-immobilizing the electron mediator ( i.e., 1, 1′-dimethyl-ferrocene, DMFc) and enzymes ( i.e., glucose oxidase, GOD) onto the carbon fibre microelectrode (CFME) surface and coupled with a microsized Ag/AgCl reference electrode the dual electrode system OCPS is readily formed. The as-prepared COF-based OCPS is very sensitive to glucose with a linear range of 1.08 μM to 8.5 mM. Moreover, the COF-based OCPS is highly selective for glucose over other endogenous electroactive species in the cerebral system. In the end, we demonstrate that our biosensor is capable of selectively monitoring glucose in the brain of rat in real time and does not need extra voltage or oxygen.